Implementasi Standar Jasa Investigasi (SJI) 5300 – 5400 Tahun 2021 dalam Audit Investigasi : Studi pada Kasus Fraud PT XYZ di Bidang Manufaktur - Putra, Alexander Alley Retta Buana; Okabrian, Soni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Fraud remains a significant risk in the corporate environment, especially in the manufacturing sector, where complex operations and financial systems can create opportunities for misconduct. To address this, investigative audits guided by established standards are crucial. This study aims to evaluate the implementation of the Investigation Service Standards (Standar Jasa Investigasi or SJI) 5300 and 5400 of 2021 during an investigative audit of a fraud case at PT XYZ, a manufacturing company. The audit was conducted by the Public Accounting Firm Bharata, Arifin, Mumajad & Sayuti (KAP BAMS). Using a descriptive method with a case study approach, data were collected through interviews, observations, and literature review. The findings reveal that the standards were generally implemented effectively. However, two procedural elements specifically the independence declaration and the traceback procedure were not applied due to contextual constraints during the audit. Despite these omissions, adherence to these procedures remains a mandatory aspect of the standards. The implications suggest a need for improved flexibility in the application of investigative standards to accommodate situational challenges without compromising professional integrity. This study highlights the importance of continual training and internal controls to ensure full compliance with investigative audit standards in practice.